Increased brain activity to unpleasant stimuli in individuals with the 7R allele of the DRD4 gene. Issue 1 (30th January 2015) - Gehricke, Jean-G.; Swanson, James M.; Duong, Sophie; Nguyen, Jenny; Wigal, Timothy L.; Fallon, James; Caburian, Cyrus; Tugan Muftuler, Lutfi; Moyzis, Robert K.
Abstract: The aim of the study was to examine functional brain activity in response to unpleasant images in individuals with the 7-repeat (7R) allele compared to individuals with the 4-repeat (4R) allele of the dopamine receptor D4 ( DRD4 ) gene (VNTR in exon 3). Based on the response ready hypothesis, individuals with the DRD4 -4R/7R genotype were expected to show greater functional brain activity in response to unpleasant compared to neutral stimuli in specific regions of the frontal, temporal, parietal and limbic lobes, which form the networks involved in attentional, emotional, and preparatory responses. Functional Magnetic Resonance Imaging activity was studied in 26 young adults (13 with the DRD4 -4R/7R genotype and 13 with the DRD4 -4R/4R genotype). Participants were asked to look at and subjectively rate unpleasant and neutral images. Results showed increased brain activity in response to unpleasant images compared to neutral images in the right temporal lobe in participants with the DRD4 -4R/7R genotype versus participants with the DRD4 -4R/4R genotype. The increase in right temporal lobe activity in individuals with DRD4 -4R/7R suggests greater involvement in processing negative emotional stimuli. Intriguingly, no differences were found between the two genotypes in the subjective ratings of the images. The findings corroborate the response ready hypothesis, which suggests that individuals with the 7R allele are more responsive to negative emotional stimuli compared to individuals with the 4R allele of the DRD4 gene.